Avaliação multicritério para apoiar a gestão da implementação das políticas de desenvolvimento sócio econômico de um plano diretor municipal - Cunha, Fernanda (2017)
In order to provide access to basic services for the population and ensure that municipalities fulfill their social function, the Master Plan was established as a basic tool for urban development and expansion that integrates the municipal planning process. As a goal to develop a Performance Evaluation model to support the management of the implementation of socioeconomic development policies of the Biguaçu Municipal Master Plan, based on the Multicriteria Methodology to Support the Constructivist Decision (MCDA-C). This research was supported in the ProKnow-C (Knowledge Development Process-Constructivist) and MCDA-C (Muti-Criteria of Decision Support - Constructivist) tools. ProKnow-C enabled the construction of a Bibliographic Portfolio -PB on the subject of Public Sector Performance Evaluation in the regional / local context, where the Bibliometric and Systemic analyzes were carried out, identifying knowledge gaps and opportunities for scientific contribution through Six analysis lenses. The MCDA-C was used in the construction of the case study carried out in the Municipality of Biguaçu. It is an exploratory research, in the form of a case study, with a qualitative and quantitative approach, involving the collection of primary and secondary data. The results highlight: (i) the identification of a PB composed of 32 scientific articles; (Ii) the performance of the systemic analysis of PB revealed the lack of constructivist models; (Iii) in the construction of the model were identified 44 Primary Elements of Evaluation - EPAs, 7 areas of concern; 75 descriptors; And (iv) the identification of 2 descriptors in Compromising Level and 73 descriptors in Competitive Level. The built model was adequate to deal with the complexity of the operationalization of the Master Plan, specifically in relation to the Socio - Economic Development axis, subsidizing the decision maker in the monitoring and evaluation of the implementation process.